The psychological implications of violence in intimate homoafective relationships between men (Research, Society and Development, 2022)
The theme that focuses on the existence of violence in intimate homosexual relationships between men is a little explored and marginalized aspect, in view of this, the study about this is paramount and important, thus, it has as its proposal and general objective: analyze which ones are men as psychological arising from violence in intimate homosexual relationships. To carry out an integrative review, formulated in six methodologies, where literature was analyzed through the inclusion and exclusion of 12 articles on the subject. The research was carried out in June 2022, through the following databases: Latin American Caribbean Literature in Science and Health (LILACS), Medical Literature Analysis and Retrievel Sistem Oline (MEDLINE) through the Virtual Health Library (BVS); Scientific Electronic Library Online (SciELO), Electronic Journals in Psychology (PEPSIC) and Google Scholar. The main results of men are considered the context of intimate violence are subject to changes found, and can be perpetuated through incorporation into the physical sphere, thus becoming a public health problem subject to intervention and a critical social view.